Improving Operational Efficiency of Nickel Ore Port in North Konawe with VSM And Optimization Approach - Kusumadewi, Karina; Zagloel, Teuku Yuri M. (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Indonesia, the world's largest nickel producer, has enforced a nickel ore export ban since 2020 to promote domestic downstream processing. This policy surge has intensified port activities, especially in nickel ore logistics, leading to operational inefficiencies such as prolonged barge waiting times, demurrage penalties, and logistics delays at key ports like Lameruru, Southeast Sulawesi. This study applies Lean principles and Value Stream Mapping (VSM) to identify waste and bottlenecks in nickel ore port operations. The research further develops a Genetic Algorithm (GA)-based optimization model to improve barge scheduling and minimize waiting times. Data collected from port operations, stakeholder interviews, and secondary sources reveal that waiting times at the jetty constitute the primary inefficiency, causing nearly half of shipments to incur demurrage. The GA optimization reduced total barge waiting time by 55%, increased immediate docking by 71%, and significantly decreased maximum waiting times, boosting port productivity and reducing costs. The Future State VSM reflects a 79.7% Process Cycle Efficiency, an improvement over the current 69.97%. Despite limitations such as reliance on static historical data and exclusion of real-time dynamic factors, this integrated Lean-VSM-GA approach demonstrates significant potential to enhance Indonesia’s nickel ore logistics, offering actionable strategies for port operators and policymakers to increase competitiveness in the global nickel industry.